Bride kidnapping from the Ossetians in historical retro-perspective and modern transformations - Tamara Т. Daueva (Кавказология, 2024)
This article looks at the stealing of women among the Ossetian ethnic group. The study’s major sources were the results of the ethnographic expedition in 2022-2023 on the territory of North Ossetia, the author’s observation materials, and the findings of the 2015 expedition in Turkey among the Ossetian diaspora. Using an empirical research approach, the essay examines the remarks - reasons for the interview question: “Is the abduction of girls a national tradition of Ossetians?”. Undoubtedly, the issue is timely, owing to the prevalence of theft today. The study’s goal is to undertake a retrospective investigation of the reasons for theft using source material, as well as to evaluate how traditional culture, which has been perpetuated by the ethnos for ages, reacts to changes in the social soil. The comparison of the couple’s and their parents’ behavioral forms in the past and present during the abduction takes up a significant portion of the research. The conclusion is formed that, today, theft is fictional, and that the reason for choosing such a form is not so much economic, but rather a result of family and household issues. The author believes that one of the most significant implications of the popularization of theft is the progressive loss of traditional rites and rituals unique to Ossetians’ traditional wedding culture.